Enabling access to new WHO essential medicines: the case for nicotine replacement therapies - Cravioto Alejandro; Bitton Asaf; Kishore Sandeep P; Yach Derek (BMC, 2010)
Abstract Nicotine replacement therapies (NRT) are powerful tools for the successful treatment of nicotine addiction and tobacco use. The medicines are clinically effective, supported by the Framework Convention on Tobacco Control, and are now World Health Organization-approved essential medicines. Enabling global access to NRT remains a challenge given ongoing confusion and misperceptions about their efficacy, cost-effectiveness, and availability with respect to other tobacco control and public health opportunities. In this commentary, we review existing evidence and guidelines to make the case for global access to NRT highlighting the smoker's right to access treatment to sensibly address nicotine addiction.